Response of Rapeseed (Brassica napus L.) and Phosphorus Fractionation in an Alkaline Soil Amended with Rock Phosphate and Elemental Sulphur - L. Habib and G.A. Alloush, R. Nasser (Journal of the Indian Society of Soil Science, 2018)
A field experiment was conducted to investigate the response of rapeseed (Brassica napus L.) to applicationof Syrian rock phosphate (RP) mixed with three rates of elemental sulphur (10, 20 and 50% S) in analkaline calcareous soil compared to triple superphosphate (TSP). The RP was applied @ 800 mg P kg-1soil. The transformations of various pools of phosphorus (P) were also studied after the harvest of rapeseedgrown for two consecutive seasons. The P fractionation scheme divided calcium phosphate into three typesnamely, dicalcium phosphates (Ca2-P), octacalcium phosphates (Ca8-P) and apatite (Ca10-P). The resultsshowed that rapeseed plant utilized P from Syrian RP as good as that of TSP in both seasons. Mixing ofelemental S with RP showed no effects on dry matter yield in first season, whereas in the second season, allmixing rates of S increased dry matter production significantly. Mixing of RP with S influenced RPdissolution, thereby all inorganic P (Pi) fractions increased. The dominant P fractions in RP and RP+Streatments were Ca10-P, followed by Ca8-P. The opposite was true for TSP treatment. The Ca2-P was themain source of available soil P as it correlates significantly with Olsen-P.